Flexibility, torque and kick performance in soccer: Effect of dominance - Oliveira, A. S C [UNESP]; Barbieri, F. A. [UNESP]; Gonçalves, M. [UNESP] (Elsevier, 2013)
Aim: The aim of this study was to evaluate the knee flexor and extensor torques in isometric contractions, comparing the H:Q ratios, flexibility and maximal kick between dominant (DL) and non-dominant (NDL) limb of soccer players (SG) and active people (AG)Methods: Subjects performed maximal instep kicks with each limb, flexibility tests and maximal isometric voluntary contractions of the knee flexion and extension at 45° and 90° to determine peak torque of the DL and NDLKnee flexion torque was divided by the knee extension torque to calculate torque ratios (H:Q ratio)Results: The flexibility and maximal kick in SG was significantly higher than in AG for both the DL and NDL (P<0.05)The maximal kick of DL was significantly higher than in NDL in SG (P<0.01)Knee flexion torque in SG was significantly higher than in AG in the DL (P<0.05), and the H:Q ratio was similar between AG and SGConclusion: Dominance related differences were evident in the flexor torque and maximal kick for SG, probably related to the asymmetric demand in trainings, which present no effect on the flexibility© 2013 Elsevier Masson SAS.
Keywords: Asymmetry; Knee joint; Soccer; adult; athletic performance; controlled study; extensor muscle; flexor muscle; human; human experiment; joint mobility; knee function; male; muscle isometric contraction; normal human; physical performance; priority journal; soccer; torque